Escaping the repugnant conclusion: Rank-discounted utilitarianism with variable population - Geir B. Asheim; Stéphane Zuber (Center for Economic Studies and ifo Institute (CESifo), 2012)
Evaluation of climate policies and other issues requires a variable population setting where population is endogenously determined. We propose and axiomatize the rank-discounted critical-level utilitarian social welfare order. It is shown to fill out the space between critical-level utilitarianism and (a version of) critical-level leximin. Moreover, it satisfies many conditions and principles used to evaluate variable population criteria. In particular, it avoids the repugnant conclusion even when the critical level is zero.
Keywords: D63; D71; H43; Q56; 330; social evaluation; population ethics; critical-level utilitarianism; social discounting; Soziale Wohlfahrtsfunktion; Utilitarismus; Bevölkerung; Soziale Diskontrate; Klimaschutz